Tanker-şamandıra Bağlama Sistemlerinin Yapay Sinir Ağları Tekniğiyle Optimizasyonu - Yetkin, Murat (Fen Bilimleri Enstitüsü, 2015)
Çok karmaşık problemlerin çözümü günümüzde gelişen teknoloji ve bilgisayarlar ile daha basit hale gelmiştir. Birçok yöntem ve algoritma kullanılarak hızlı ve efektif çözümler üretilebilmektedir. Bu yöntemlerden biri de yapay sinir ağları tekniğidir. Temelde biyolojik sinir hücresini esas alan yapay sinir ağları, yapay sinir hücreleri arasında bağlantılar kurarak öğrenilen durumlara uygun sonuçlar verebilmektedir. Yapay sinir ağları hakkında ilk çalışma 1943 yılında nörofizikçi McCulloch ve matematikçi Pitts tarafından yapılmıştır. Yıllar geçtikçe yeni yöntemler ve algoritmalar geliştirilmiş ve yapay sinir ağları bugünkü halini almıştır. Yapay sinir ağlarının birçok kullanım alanı bulunmaktadır. Bunların bazıları sınıflandırma, kümeleme, tahmin, desen tanıma, fonksiyon yaklaşımı ve optimizasyondur.  Yapay sinir ağları doğrusal olmaması, öğrenebilmesi, genelleme yapabilmesi, uyarlanabilmesi, hata toleransının az olması ve hızı nedeniyle güçlü bir tekniktir. Özellikle hata toleransının az olması ve problemlere hızlı bir şekilde sonuç bulması yapay sinir ağlarını diğer algoritmalara göre bir adım öne çıkarmaktadır. Yapay sinir ağları yapısal olarak üç katmandan oluşmaktadır. Bu katmanlar; giriş katmanı, ara (gizli) katman ve çıkış katmanıdır. Veri akışı katmanlar arasında devamlı şekilde devam etmektedir. Yapay sinir ağları yapısında temel olarak beş işlem elemanı bulunmaktadır. Bunlar girdi verileri, ağırlıklar, birleştirme fonksiyonu, aktivasyon fonksiyonu ve çıktı verileridir. Girdi verileri giriş katmanına gelerek ağırlıklar ile birleşir ve birleştirme fonksiyonu yardımı ile aktivasyon fonksiyonuna gönderilir. Aktivasyon fonksiyonundan geçtikten sonra çıktı verileri olarak alınırlar. Üç çeşit öğrenme türü bulunan yapay sinir ağlarında en çok kullanılan öğrenme türü eğitmenli öğrenmedir. Diğer öğrenme türleri ise eğitmensiz öğrenme ve yarı eğitmenli öğrenme olarak bilinmektedir. Ayrıca yapay sinir ağlarında bilinen bir çok öğrenme kuralı bulunmaktadır. Bu kurallardan en çok kullanılanları Hebb kuralı, Hopfield kuralı, Kohonen kuralı, delta kuralı, Levenberg-Marquardt algoritması ve geri yayınım algoritmasıdır. Ağ yapılarına göre ileri ve geri beslemeli olmak üzere ikiye ayrılmaktadır. İleri beslemeli ağda veriler bir sonraki katmana aktarılırken, geri beslemeli ağda veriler bir sonraki katmana aktarıldığı gibi kendinden önce bulunan katmanlara da aktarılabilir. Tek katmanlı modeller ile başlayan yapay sinir ağı çalışmaları daha sonra çok karmaşık problemlere de çözüm bulunamadığı için çok katmanlı yapıları da ortaya çıkarmıştır. Tek katmanlı yapılarda perceptron, ADALINE ve MADALINE modelleri ilk bilinen modellerdir. Çok katmanlı yapılarda ise giriş ve çıkış katmanları arasında birden çok ara (gizli) katman bulunabilmektedir.  Yapay sinir ağlarının paralel olarak bilgiyi işlemesi, öğrenebilmesi, eksik bilgiler ile çalışabilmesi, yeni örneklere çabuk uyum sağlayabilmesi ve matematik modele ihtiyaç duymaması gibi özellikleri avantajları olarak söylenebilir. Dezavantajları ise sistem içinde ne olduğu bilinmediği için ağın verdiği sonuçları işleminin zorluğu, eğitilmek için zamana ihtiyaç duyması ve yalnızca nümerik bilgiler ile çalışması gösterilebilir. Çok noktalı tanker-şamandıra bağlama sistemi dizaynında birçok parametre önem arz etmektedir. Bunlardan bazıları rüzgar, dalga karakteristiği, akıntı, bağlama halatlarının bağlanma noktası ve bağlama açısı olarak gösterilebilir.  Bu çalışmada OrcaFlex programı ile 4 noktalı tanker-şamandıra bağlama sistemleri modellendikten sonra değişik çevre şartları ve farklı bağlama şekilleri ile simülasyonlar yapılmıştır.  Bu simülasyonlardan elde edilen sonuçlar yapay sinir ağlarını eğitmede kullanılmış ve bir algoritma elde edilmiştir. Bu algoritma ile farklı bağlama şekilleri simülasyona gerek kalmadan, kullanılacak parametreler belirli aralıkta yapay sinir ağlarına veri olarak girilerek optimum bağlama şekli seçilebilir.

Artificial Neural Network (ANN) is an artificial representation of human brain that tries to simulate its learning process. The most basic element of human brain is a specific type of cel, which provides us with the abilities to remember, think and apply previous experiences to our every action. These cells are known as neurons. ANN use artificial neurons to create a network like human’s nervous system.  The first study about ANN was produced in 1943 by neurophysicist McCulloch and matematician Pitts. After that many studies about ANN were carried out. There are some important studies about ANN respectively, Hebbian Rule (1949), ADALINE (1960), Perceptron (1969) “Neural Networks and Physical Systems” (1982). Artificial neural networks are used in many discipline and sciences. There are many problems that solved by ANN in matematics, medicine, business and finance. The main areas of ANN’s are classification, clustering, forecast, function approximation and optimization.  The basic properties of ANN are modelling of nonlinear problems, parallel structure, employment of missing information, error tolerance, learning and generalization. These properties show ability of ANN about solving complex problems. Architecture of ANN is seperated in 3 layers. The first part is input layer. This layer takes data from external environment. The second layer is hidden layers. There may be multiple hidden layers. The last layer is output layer. The output layer consists of neurons that communicate the output of the system to the user or external environment.  There are 5 process elements in ANN. One of them is inputs. Inputs are coming from external environment to neurons. Other element is weights which transfer inputs to process element. Weights show mathematics coefficient of inputs. Joining function sums the inputs after multiplication of weights. Activation function is applied a process to sum which comes from joinning function. There are a few activation functions in use. Sigmoid activation function is the most commonly used function. Sigmoid function could differantiate and both sigmoid function and its differantiation are continuous. The other common activation function is tangent hyperbolic activation function. This function works like sigmoid function but gives results in [-1,1] interval where sigmoid function gives [0,1]. The last element of ANN is output which is the value obtained after activation function process. Learning types of ANN are divided in 3 groups. First group is supervised learning. This learning requires both inputs and outputs to make an algorithm. Another group is unsupervised learning. Unsupervised learning takes inputs without outputs and create an algorithm. Last group is semi-supervised group which like unsupervised learning but this make a comparison with outputs. Also, there are many learning rules usable in ANN. First learning rule was produced by Canadian psychologist Donald Hebb in 1949 which calls as “Hebb Rule”. This rule’s basic is that if there are two neurons inform each other and both active, the network between them should be more strength. Hopfield rule is similar to Hebb rule. If inputs and outputs are both active or passive the network between them should strengthened or weakened. Kohonen rule say that the cell which has the biggest weight has power to impress other neighbour cells. Delta rule is a developed Hebb rule which is one of the most commonly used learning rule. This rule is similar to least squares method. Levenberg-marquardt algorithm is an approach to Newton method. Levenberg-Marquardt algorithm is a method that research minimum. This algorithm uses Hessian matrix. The other rule is back propagation algorithm. In this rule, the error propagate to back. The error between real data and calculated data changes by using weights. There are two type of ANN according their network structures. First type is feed forward ANN. Feed forward ANN send data from input layer to hidden layer with no changes. Data take a process in this part and then send to output layer. Feedback ANN can send data to all layers without any consraint.  ANNs divided in 2 groups based on their layer number. ANN could be one layer or multi layers. One layer ANN gives result only 1 or 0. Perceptron, ADALINE and MADALINE are known as one layer ANN models. Multi layer ANN model has many hidden layers.  The advantages of ANN are learning ability, parallel structure, working with missing data and requiring no mathematic model. Also, ANN has some disadvantages. ANN needs time to train and has no rule in its networks. Only works with numerical data.  MatLab has a toolbox named “Neural Network Toolbox” where user can make artificial network’s training, learning, application and simulation. MatLab has two ways to use “Neural Network Toolbox”. First one is entering to command window the “nntool” command and second is starting toolbox from “Apps” part of MatLab. This thesis use ANN to optimize tanker-buoy mooring systems. Tanker-buoy mooring systems are offshore systems, so that it affected from environmental conditions. To reduce these effects tanker-buoy systems are supported by mooring lines. Mooring systems could be single point or multi points. Single point system moves to adapt environmental conditions but multi points system stay in its first point. Multi points systems are exposed like wave, current and wind forces because of no adaptation to environment. The maneuvering area is important in tanker- buoy mooring systems. Because there may be other systems around it.  OrcaFlex program is used to design tanker-buoy mooring system to simulate and get results about mooring tensions and tanker displacements. 4 points mooring system is designed. This system is used to test program with different wind speeds and gets expected tension results when wind speed increases. Before entering data to ANN, a normalization is made and data ranges are reduced to [0,1] interval. These data are used to train ANN structure and an algorithm is occured.  After creating algorithm, the results of training, test and validaton gets from ANN.  At this algorithm Levenberg-Marquardt learning is used. To make error correction least squares method used. There are 14 neurons in hidden layers.  This ANN algorithm can be used for optimization of new designs without simulation studies. Designing and simulating process in OrcaFlex take more times according to ANN structure. Artificial neural networks is fast and simple system, to use in different mooring systems.
Optimization Of Spread Mooring Systems With Artificial Neural Networks
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Yapay Sinir Ağları; Tanker Şamandıra Bağlama Sistemleri; Orcaflex; Artificial Neural Networks; Tanker Buoy Mooring Systems; Orcaflex